Large parathyroid adenomas: Potential mechanisms to reconcile adenoma size and disease phenotype - Bhan, Arti; Athimulam, Shobana; Kumari, Poonam; Pal, Rimesh; Bhadada, Sanjay Kumar; Cook, Bernard C.; Qiu, Shijing; Rao, Sudhaker D. (Frontiers in Endocrinology, 2023)
ABSTRACT: Parathyroid adenomas weighing more than 3.5 g are reported variously as “atypical”, “large” or “giant” parathyroid adenomas. All such adenomas are rare variants accounting for no more than 1.5% of all parathyroid adenomas. Atypical parathyroid adenomas are often associated with more severe form of the disease, including osteitis fibrosa cystica (OFC) and share many biochemical, histological, and molecular features of both benign and malignant parathyroid neoplasms, and are considered a distinct clinical entity. However, the pathogenesis of oversized parathyroid adenomas and the often-associated skeletal phenotype remains unclear. We present five cases of primary hyperparathyroidism (PHPT) with OFC, an uncommon manifestation of contemporary PHPT, associated with larger parathyroid adenomas, seen in the Bone and Mineral Disorders Clinic of the Henry Ford Health in the last 30 years to illustrate the critical role of vitamin D nutrition in the pathogenesis of both the OFC and adenoma size. The estimated prevalence of OFC was very low 0.002%, 5 of the >3000 surgically confirmed cases of PHPT seen during this time. The mean ± SD values were: age: 36.8 ± 22.1 years (4 of the 5 <36years), serum calcium 11.6 ± 1.1 mg/dl, alkaline phosphatase 799 ± 487 IU/L, PTH 1440 ± 477 pg/ml, 25-hydroxyvitamin D 13.0 ± 8.9 ng/ml, 1,25-dihyroxyvitamin D 26.5 ± 13.7 pg/ml, urine calcium 562 ± 274 mg/day, and parathyroid adenoma weight 4.53 ± 2.2 g. Parathyroidectomy led to the resolution of both the biochemical indices and OFC in each patient without recurrence over >10 years of follow-up. Because OFC is a very rare in the West, but very common areas of endemic vitamin D deficiency, we also examined the relationship between vitamin D nutrition, as assessed by serum 25-hydroxyvitamin D level, and parathyroid adenoma weight as well as prevalence of OFC in two large secularly diverse cohorts of patients with PHPT (Detroit, USA and Chandigarh, India). Based on this relationship and the relative prevalence of OFC in these two large cohorts, we propose that vitamin D nutrition (and perhaps calcium nutrition) best explains both the adenoma size and prevalence of OFC.